Infrastructure : Doing More with Less - Woetzel, Jonathan; Pohl, Herbert (World Bank, Washington, DC, 2014)
Adequate urban infrastructure can be expensive, but the costs of not delivering housing, transportation, water, sewage, public facilities, and other necessities are also high. Inadequate infrastructure slows and even reverses economic growth, driving unemployment, crime, and urban decay. It can fuel urban tensions by widening divisions among ethnic or income groups or between long-time residents and recent immigrants. And it can foster a general malaise that drains a city's vitality and spirit. One study in Africa showed that the return on investment for infrastructure was about 50 percent, based on contributions to gross domestic product (GDP), and that if investments were optimized, the return will be closer to 150 percent. This value is delivered through increased productivity and job creation, among other channels. Social benefits from improved public services and living standards are also substantial. In emerging markets, inadequate infrastructure can be a substantial barrier to growth. Adequate infrastructure reduces costs, supports economic activity, increases factor productivity in cities, and connects cities to domestic and international markets. With the staggering demand for infrastructure in emerging economies, officials will need to continue gathering as much funding as possible to meet their needs. This paper looks closer at the infrastructure needs of cities in emerging markets, based on the most recent McKinsey Global Institute (MGI) analysis. It offers practical suggestions on how to answer fundamental questions facing any government trying to get the greatest impact from limited infrastructure funds. And before concluding, it examines how cities worldwide have improved governance, institutions, processes, and capabilities to help close the infrastructure funding gap.